PCR detection of Ralstonia solanacearum: A new approach for rapid detection of bacterium from infected plants - DUTTA, RAM; BANERJEE, AMRITA; BEHERE, GAJANAN T; DEVI, K JINA; CHANDRA, SATISH; NGACHAN, S V (The Indian Journal of Agricultural Sciences, 2015)
Ralstonia solanacearum (Smith) is a soil-borne plant pathogen responsible for causing bacterial wilt and having wide host range which includes monocots, dicots, annual plants/trees and shrubs. It is a most destructive disease of solanceaous crops and ginger in north eastern region of India. The pathogen is primarily present in soils as saprophytic bacterium and it has ability to survive for long periods of time in various natural habitats. The bacterium causes sudden wilting in plants and difficult to detect at the initial level as similar symptom may also occur with many fungal organisms like Fusarium spp. and Verticillium spp. An attempt was made to develop a PCR-based rapid method for detection of this pathogen. This method requires only 3-5 hours against the conventional methods which generally require minimum 3 days to detect the pathogen. The PCR uses previously reported primer pairs for fliC gene (Rsol_fliC), which amplify 400bp region of fliC gene. The bacterial ooze from infected tissues was directly used as a source of DNA. The amplified product was cloned and sequenced for confirmation. The PCR based method developed in this report is very simple, robust and inexpensive and was successfully tested on four infected samples and further validated on over 50 samples of tomato which were infected by R. solanacearum.